Descrição de novas espécies de bactérias: o gênero Mycobacterium como exemplo - Tortoli, Enrico (Revista Pan-Amazônica de Saúde, 2019)
Opinion article written by Speaker for the II International Scientific Meeting of Instituto Evandro Chagas, held from October 25 to 27, 2017, in Ananindeua, Pará, Brazil. All the articles of this modality were analyzed by the Scientific Committee of the Event and, later, by the Editors of RPAS.